ANALYSIS OF QUALITY CONTROL COMPUTERIZED TOMOGRAPHY SCAN (CT SCAN) RESULTS IN INDONESIA BASED ON NATIONAL AND INTERNATIONAL STANDARDS (Al Insyirah International Scientific Conference on Health, 2021)
The purpose of this study is to assess the results of the implementation of Quality Control Computerized Tomography Scan (CT Scan) in Indonesia based on national and international standards. The method used is a literature study of quality control CT scan research results from 2012 to 2020 with various types of CT scans in Indonesia. The data obtained from the literature study carried out an in-depth analysis of compliance with national and international standards. The results of the analysis show that the standard implementation of QC CT Scan in Indonesia has a more complex parameter test than the ACR and IAEA standards. Based on the 2018 Bapeten Standard (RS3), the QC CT1 Implementation Rate is above 50%. Whereas in the ACR standard (RS1) there are 2 types of CT that are above 50% and in the IAEA standard (RS3) there are 7 CTs that are above 50%. The result of the parameter test based on RS3 standard, CT1 passed the test, CT2 there were 4 parameters that did not pass the test, namely PT2, PT5, PT14 and PT17. CT3 to CT 8 and CT 10 the QC results passed the test, while CT9 parameter PT9 did not pass the test. However, for CT2 to CT10, many QC parameters were not implemented. Based on the data analysis above, it can be concluded that the level of QC implementation based on national and international standards are very low.
Keywords: quality control CT scan; CT implementation rate; standard